A mild, environmental, and low-destructive recycling strategy for the 3D multiaxial braided composites cured by the vacuum-assisted resin transformed molding process. (November 2022) - Lu, Yao; Liu, Tao; Wang, Shujuan; Sun, Yan; Zhang, Yanfeng; Kang, Jingyu; Li, Bo; Gao, Yuan; Gao, Xingzhong; Fan, Wei
Abstract: Recycling the 3D textile preform from the used composites is one kind of novel technique to reduce the manufacturing cost of 3D textile composites. This work designed the 3D multiaxial braided composite (3DMBC) that was manufactured by the 3D multiaxial braided preform and the epoxy vitrimer resin to realize the recycling of the preform that can be reconsolidated to the composites. The recycling was realized through an alcoholysis reaction with the aid of ethylene glycol solution in a vacuum environment of 180 °C for 72 h. The retention of compressive strength of the recycled 3DMBC was 92% indicating that the recycle method was low-destructive. The designed epoxy vitrimer resin in this work can be used through the vacuum-assisted resin transformed molding process, making recycling of 3D textile composites possible. Graphical abstract: Image 1 Highlights: The chemical recycling strategy for 3D textile composites was firstly realized. The recycling mechanism of the epoxy vitrimer resin composites was revealed. The recycling strategy for 3D textile composites is mild, environmental and low-destructive.